How the fuel prices, interest rates, and exchange rate affect inflation and economic growth - Lubis, Judikson (Fakultas Ekonomi dan Bisnis Universitas Palangka Raya, 2023)
The objective of this study is to examine the impact of fuel costs, interest rates, and exchange rates on both inflation and economic growth in the province of Central Kalimantan. The research use path analysis as the methodology. Path analysis is a technique employed to ascertain the direct and indirect association between the independent factors and the dependent variable while considering the presence of a mediating variable. The data utilized in this investigation is classified as secondary data. The data are sourced from publications by the Central Statistics Agency (BPS), Bank Indonesia (BI), and Pertamina. The research employed the Path Analysis methodology. The findings of this study suggest that fuel prices exert a direct, positive, and statistically significant impact on inflation. Interest rates exert a direct and substantial impact on inflation. The Exchange Rate has a direct and negligible impact on Inflation. Fuel prices exert a direct and substantial impact on economic growth. Interest rates exert a direct and negligible impact on economic growth. The Exchange Rate exerts a direct and substantial adverse impact on Economic Growth. Inflation exerts a direct and substantial adverse impact on economic growth. Fuel prices have little direct impact on economic growth via inflation. Interest rates do not have a direct impact on economic growth by means of inflation. The exchange rate has an indirect impact on economic growth via influencing inflation.